Effects of the Humanized Anti-Adrenomedullin Antibody Adrecizumab (HAM8101) on Vascular Barrier Function and Survival in Rodent Models of Systemic Inflammation and Sepsis. Issue 6 (December 2018) - Geven, Christopher; Peters, Esther; Schroedter, Mathias; Struck, Joachim; Bergmann, Andreas; McCook, Oscar; Radermacher, Peter; Kox, Matthijs; Pickkers, Peter
ABSTRACT: Purpose: Adrenomedullin (ADM) is an important regulator of endothelial barrier function during sepsis. Administration of a murine antibody targeted against the N-terminus of ADM (HAM1101) resulted in improved outcome in models of murine sepsis. We studied the effects of a humanized form of this antibody (HAM8101, also known as Adrecizumab) on vascular barrier dysfunction and survival in rodent models of systemic inflammation and sepsis. Methods: Rats (n=48) received different dosages of HAM8101 or placebo (n = 8 per group), directly followed by administration of lipopolysaccharide (5 mg/kg). Twenty-four hours later, Evans Blue dye was administered to assess vascular leakage in kidney and liver tissue. Furthermore, mice (n = 24) were administered different dosages of HAM8101 or placebo (n = 6 per group), immediately followed by cecal ligation and puncture (CLP). Eighteen hours later, albumin, vascular endothelial growth factor (VEGF), and angiopoietin-1 were analyzed in the kidney. Finally, effects of single and repeated dose administration of HAM1101, HAM8101 and placebo on survival were assessed in CLP-induced murine sepsis (n = 60, n = 10 per group). Results: Dosages of 0.1 and 2.5 mg/kg HAM8101 attenuated renal albumin leakage in endotoxemic rats. Dosages of 0.1, 2.0, and 20 mg/kg HAM8101 reduced renal concentrations of albumin and the detrimental protein VEGF in septic mice, whereas concentrations of the protective protein angiopoietin-1 were augmented. Both single and repeated administration of both HAM1101 and HAM8101 resulted in improved survival during murine sepsis. Conclusions: Pretreatment with the humanized anti-ADM antibody HAM8101 improved vascular barrier function and survival in rodent models of systemic inflammation and sepsis.